Theoretical aspects of solving economic problems of nature management: evolution of scientific views - Tetiana Koniakhina (Cхід, 2013)
In scientific study evolution of the environmental studies in political economy is studied. Classic (Thomas Malthus, David Ricardo, J.S. Mille, G. George, A. Marshall, K. Marx) and neoclassical (A. Pigou, R. Coase, M. Dobby, J. Hershlifer, W. Baumol, W. Outts, T. Titenberh, D. Pearce, K. Turner, etc.). directions of analysis of environmental issues focused on her very dissimilar ecological and economic criteria, often offering and arguing diametrically opposed concepts and methodological revisions. However, the active scientific debate from different schools within economics were generated relatively autonomous fields of scientific opinions that explored a range of issues of contemporary nature: a theory of property rights which explains the root cause of modern ecological and economic crisis; public choice theory, which considers the procedure detection and identification of public including environmental benefits; welfare theory, which puts to allocate scarce natural raw materials, based on the principles of equality and social justice.